Loteamentos regulares, irregulares, áreas institucionais e lotes em pequenas cidades: a produção da cidade de Santa Bárbara-BA por meio do parcelamento do solo - Rebelo, Diego Santos (2023)
This dissertation aims to analyze the legal and technical basis for the approval of subdivisions in small cities, taking into account the forms of occupation and division of urban land. To do so, it analyzes the production of urban space in the city of Santa Bárbara through the subdivisions created between the years 2010 and 2020. The goal was to identify the subdivisions produced during this period using the urban land subdivision law (LPSU) and local legislation for the approval, installation, and monitoring of subdivisions created during the period of analysis, in order to verify requirements of legality, illegality, and irregularity that could respond to the interests and demands of the municipality and developers in the reproduction of urban space. Based on this information, the city was identified as small, relying on the legal aspect, although we have criticisms of this concept. Small cities are exempt from producing an urban development master plan (PDDU) due to having a population of less than 20,000 inhabitants, according to Article 182, § of the Federal Constitution and the Statute of the City (Law 10.257/2001). In the absence of the aforementioned and the hesitant proposal of successive administrations to create a PDDU, the legal framework for regulating lots in the city and their use in guiding the approval of urban subdivisions was identified, understanding the strategy used by actors in implementing these ventures. In a more detailed analysis, the study identified the subdivisions and developers, their origins, and the development of a path that responded to the way of urban expansion through land subdivision. The study filtered the subdivisions of the period and verified, documentally and through interviews, the existence of eight formalized subdivisions. The aim of the analysis was to identify which of them were irregular, legal, or illegal, and the impacts caused by the absence of essential items to comply with the minimum required by the land subdivision law. As a result of this study, external interests in the marketed lots could be identified. Of the eight authorized subdivisions, only one strictly complied with the combined procedure of municipal regulations and the LPSU. The city was expanding without control over the land use procedure and exceeding the limits of the expansion area. Moreover, it resulted in the characterization of lots that do not correspond to the norm and respond to the characterization of the production of urban space through irregular and illegal expansion of subdivisions. Despite criticisms of the process of legalizing land without accompanying study phases, it leads the city to an uneven characterization and distant from the technical characteristics and legal basis on which the subdivisions are anchored.